blast pathogen characterization in Colombia - CGIAR Research Program on Rice (2021)
Pathogen virulence profiles identified on isolates obtained from two rice growing areas in Colombia where the disease is not prevalent, but affects farmers fields when climatic conditions favor infections (occasional blast). Strains with those profiles should be used to screen germplasm, new varieties and advanced lines, developed for those regions.